Unknown attack detection model based on network behavior analysis - Yi-han YU; Yu FU; Xiao-ping WU (网络与信息安全学报)
As for the intranet security threats of the increasing number of unknown attacks,an unknown attack detection model based on network behavior analysis was proposed.With the help of the information resources within the intranet,firstly,the information resources of the intranet were collected,then the risk factors of abnormal behav-ior of the internet information node were analyzed,finally,the information node and the information resources ac-quisition path as the key element were used to construct the detection model of the directed graph.By verifying,the model can achieve the desired detection results.